Suiting Library Instruction to the Myers-Briggs Personality Types and Holland Vocational Personality Types of Engineering Students - Jeanine Williamson (Issues in Science and Technology Librarianship)
The Myers-Briggs personality typology and the Holland Vocational typology of work environments and individuals offer insights about engineering students and faculty that librarians may apply to instruction. This article provides a literature review of the two theories as applicable to library instruction; discusses the personality make-ups of engineering students, Engineering faculty, and librarians; discusses selected literature relating the two theories to learning; and provides possible applications of the Myers-Briggs system and the Holland Vocational system to information literacy or library instruction for engineering students.